Analisis Risiko Kerja Petugas Filling Rawat Inap Dengan Menggunakan Severity Assessment di RSUP Dr. Hasan Sadikin Bandung - Inggil De Crystal; Efri Tri Ardianto; Sustin Farlinda (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Risk is the possibilities of an unwanted, or unexpected, adverse loss in an activity. Risk can occur as a form of thepossibility of something bad happening in the future which can not be predicted when it comes. These risks can beresulted as negative impacts for the existing officers in several activities. We have observed the examples of risks thatoccur in the filling room of Dr. Hasan Sadikin General Hospital, Bandung. There are several risks of occupationalaccidents experienced by officers such as fingers affected by stapler attached to the medical record files, officers feelaches and pain in their hands and back when retrieving files, and the possibility of officers being hit by files. Thisresearch was aimed to analyze the risks that occur in filling inpatients. This risk assessment uses severity assessmentand a hierarchy of risk control to overcome the risks that occur. The type of research uses qualitative research with 4respondents. The results of this study produced 7 risks with 4 high injury risks and 3 moderate injury risks. Handling inrisk prevention is needed by making work safety SOPs, mandatory of Personal Protective Equipment (PPE) usage, theuse of tools to lift heavy loads, the use of chairs and stairs with strong materials, giving warning signs, paying attentionto ventilation to regulate proper lighting, and installing thermometers in inpatient filling rooms.